Correlation Between The Body Height Of Pregnant Mother With The Case Of Cephalopelvic Disproportion (CPD) At The General Hospital In Mandau Subdistrict Bengkalis Regency - Erick Caesarrani Asmara; Mofrilindo Mofrilindo; Nadia Annisa Ratu; Fadler Hidayat (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
Cephalopelvic Disproportion (CPD) is a condition that describes a discrepancy between maternal and fetal pelvic capacity caused by maternal pelvic abnormalities (pelvic bone size and architecture) or abnormalities in the fetal head (size or presentation) or a combination of both. The dominance of sectio caesarea surgery for cephalopelvic disproportion according to the Basic Health Research Survey in Indonesia in 2010 was quite high at 4.40% of all childbirths. Factors affecting cephalopelvic disproportion can be influenced by both mother and baby. Factors of the mother include body height less than 145 cm, and, the size of the outer and inner pelvis is below normal that the baby is unable to pass through whereas factors in the baby is that the large baby size. Previous studies on pregnant women found that the majority of those who experienced cephalopelvic disproportion were mothers with short postures or a body height of less than 145 cm. Objective : To determine the relationship between maternal height and the incidence of cephalopelvic disproportion at the General Hospital in Mandau Subdistrict, Bengkalis Regency period 1 January - 31 December 2017. Method : This type of research is analytic observational with cross sectional design. The sampling technique used is simple random sampling. The sample in this study amounted to 253 respondents. Data for height and incidence of CPD using medical record records of Mandau District Hospital Bengkalis Regency period 1 January - 31 December 2017. The data obtained will then be analyzed using the Spearman correlation test. Results : There was a significant relationship between the height of pregnant women with the incidence of CPD in the District Hospital of Mandau, Bengkalis Regency, period 1 January - 31 December 2017 with a p value of 0.00 (p <0,01) and correlation coefficient (r=-0,737) with strength relationship is very strong and negative direction. Conclusion : There is a significant relationship between the height of pregnant women with the incidence of CPD in the District Hospital of Mandau, Bengkalis Regency, period 1 January - 31 December 2017.